Enabling meaningful use of AI-infused educational technologies for children with blindness: learnings from the development and piloting of the PeopleLens curriculum - Morrison, Cecily; Cutrell, Ed; Grayson, Martin; Becker, Elisabeth RB; Kladouchou, Vasiliki; Pring, Linda; Jones, Katherine; Faia Marques, Rita; Longden, Camilla; Sellen, Abigail (ASSETS 2021, 2021)
Novel AI-infused educational technologies can give children with blindness the opportunity to explore concepts learned incidentally through vision by using alternative perceptual modalities. However, more effort is needed to support the meaningful use of such technological innovations for evaluations at scale and later wide-spread adoption. This paper presents the development and pilot evaluation of a curriculum to enable educators to support blind learners’ self-exploration of social attention using the PeopleLens technology. We reflect on these learnings to present four design guidelines for creating curricula aimed to enable meaningful use. We then consider how formulations of “success” by our participants can help us think about ways of assessing efficacy in low-incidence disability groups. We conclude by arguing for our community to widen the scope of discourse around assistive technologies from design and engineering to include supporting their meaningful use.